Compound heterozygous CFTR variants (Q1352H and 5T; TG13) in a Chinese patient with cystic fibrosis - Run Guo; Yingxue Zou; Yongsheng Guo; Weiwei Gao (BMC, 2024)
Abstract Cystic fibrosis (CF) is an autosomal recessive inherited disease caused by variants of cystic fibrosis transmembrane conductance regulation (CFTR) gene. This report presents a case of a Chinese boy diagnosed with CF, attributed to the presence of two specific CFTR gene variations: 4056G > C (NM_000492.4) (p.Gln1352His, legacy: Q1352H) and c.1210-34TG[13]T[5] (NM_000492.4)(legacy: 5T; TG13). A ten-year-old boy was admitted to the hospital due to recurrent pneumonia, cough, and intermittent fever for seven years. Lung auscultation revealed rales, and a lung CT scan indicated parenchymal transformation with infection in both lungs. Whole Exome Sequencing (WES) identified two CFTR gene variants, Q1352H and 5T; TG13, which were significantly associated with clinical phenotype. Following a two-year course of azithromycin combined with inhalation therapy with budesonide, the patient experienced no further episodes of respiratory infections. Moreover, significant improvements were observed in pulmonary function, pulmonary infection, and bronchiectasis. The occurrence of combined variations, Q1352H and 5T; TG13, in the CFTR gene is rare and specific to Chinese populations. WES proves to be a valuable diagnostic tool for detecting CFTR gene variants.